Modified silk fibroin scaffolds with collagen/decellularized pulp for bone tissue engineering in cleft palate: Morphological structures and biofunctionalities - Sangkert, S.; Meesane, J.; Kamonmattayakul, S.; Chai, Wen Lin (Elsevier, 2016)
Cleft palate is a congenital malformation that generates a maxillofacial bone defect around the mouth area. The creation of performance scaffolds for bone tissue engineering in cleft palate is an issue that was proposed in this research. Because of its good biocompatibility, high stability, and non-toxicity, silk fibroin was selected as the scaffold of choice in this research. Silk fibroin scaffolds were prepared by freeze-drying before immerging in a solution of collagen, decellularized pulp, and collagen/decellularized pulp. Then, the immersed scaffolds were freeze-dried. Structural organization in solution was observed by Atomic Force Microscope (AFM). The molecular organization of the solutions and crystal structure of the scaffolds were characterized by Fourier transform infrared (FT-IR) and X-ray diffraction (XRD), respectively. The weight increase of the modified scaffolds and the pore size were determined. The morphology was observed by a scanning electron microscope (SEM). Mechanical properties were tested. Biofunctionalities were considered by seeding osteoblasts in silk fibroin scaffolds before analysis of the cell proliferation, viability, total protein assay, and histological analysis. The results demonstrated that dendrite structure of the fibrils occurred in those solutions. Molecular organization of the components in solution arranged themselves into an irregular structure. The fibrils were deposited in the pores of the modified silk fibroin scaffolds. The modified scaffolds showed a beta-sheet structure. The morphological structure affected the mechanical properties of the silk fibroin scaffolds with and without modification. Following assessment of the biofunctionalities, the modified silk fibroin scaffolds could induce cell proliferation, viability, and total protein particularly in modified silk fibroin with collagen/decellularized pulp. Furthermore, the histological analysis indicated that the cells could adhere in modified silk fibroin scaffolds. Finally, it can be deduced that modified silk fibroin scaffolds with collagen/decellularized pulp had the performance for bone tissue engineering and a promise for cleft palate treatment.